Penerapan Model View Kontroler Pada Pengembangan Aplikasi Penawaran dan Penerimaan Barang - Zulfikar, Ahmad Fikri; Supriyadi, Dede (Forum Kerjasama Pendidikan Tinggi (FKPT), 2022)
The role of the internet is very important in order to produce information that is faster and more accurate, CV Lavender Bakery is a food and beverage provider. CV Lavender Bakery is currently using internet media optimally for the performance of the company, especially in the field of supply and demand for goods as a marketing medium. The process of delivering information on supply and demand has been through the company's web. The design of the information system uses the PHP programming language and data storage with MySQL. The results achieved in designing web-based supply and demand applications are good data processing and storage, and to be more efficient and structured, I will develop this web application with the MVC (Model View Controller) concept